2012
DOI: 10.1002/adfm.201202046
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Coating of Iron Nanowires for Nanorobotic Applications: Synthesis, Characterization and Magnetic Wireless Manipulation

Abstract: Wireless‐manipulated graphite coated nanomagnets are promising candidates for minimally invasive targeted drug delivery platforms. Iron nanowires coated with graphitic shells are synthesized by template‐assisted deposition. The use of porous aluminum oxide templates enables both the batch production of nanowires by electrodeposition and their subsequent conformal encapsulation in graphite using chemical vapor deposition (CVD). High quality graphitic shells are obtained when CVD conditions are optimized using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 53 publications
4
57
0
Order By: Relevance
“…Nevertheless, the experimental loops measured along the long axis of the NWs are more sheared than the calculated ones, which is an indication of dipolar interactions. 21 The results clearly reveal that shape anisotropy dominates over magnetocrystalline anisotropy, also in accordance with the micromagnetic simulations. The finite coercivity is due to the non-zero magnetocrystalline anisotropy.…”
Section: Vsm Measurements Of the Nwssupporting
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, the experimental loops measured along the long axis of the NWs are more sheared than the calculated ones, which is an indication of dipolar interactions. 21 The results clearly reveal that shape anisotropy dominates over magnetocrystalline anisotropy, also in accordance with the micromagnetic simulations. The finite coercivity is due to the non-zero magnetocrystalline anisotropy.…”
Section: Vsm Measurements Of the Nwssupporting
confidence: 86%
“…For this purpose a previously optimized one-step anodization procedure was utilized. 21 Briefly, Ti/Au/Al coated Si/SiO 2 chips were anodized in 0.3 M oxalic acid at a potential of +60 V. The anodized chips were subjected to chemical etching using 5 % (v/v) phosphoric acid in order to widen the pores to the desired value of 100 nm. The area of anodization and subsequent electrodeposition was 0.5 cm 2 .…”
Section: Synthesis Of Feco/cu Msnwsmentioning
confidence: 99%
“…Apart from chemical composition, their sizes and shapes play also a signifi cant role in the possible applications. It has been already reported that nanomaterials in a form of nanowires usually exhibit superior magnetic properties in comparison with equivalent nanoparticles of similar structure, mass, and volume [5]. Therefore, iron nanowires or their oxide derivatives are supposed to be one of the most interesting magnetic nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Recently, the AAO-template route has been the most impressive way because of its low growth temperature and good potential for large scale synthesis of ordered nanostructures. [23][24][25][26][27][28] The photoluminescent properties of ZnO have received much attention because of the ability to tune the optical properties of ZnO by tailoring its band gap (direct band gap of 3.37 eV) with higher exciton binding energy (60 meV) as compared to other semiconductor materials such as ZnSe (22 meV), ZnS (40 meV) and GaN (25 meV) which make it suitable for short-wavelength optoelectronic devices and gas sensor applications. [29][30][31][32] Typically, ZnO exhibits photoluminescence characteristics in the visible and UV regions; the UV emission at 370 nm is due to radiative recombination of excitons while the green luminescence in ZnO arises due to recombination involving intrinsic defect centers such as oxygen vacancies, [33][34][35] interstitial oxygen, 36,37 zinc vacancies and interstitial zinc.…”
Section: Introductionmentioning
confidence: 99%